Riveting machine with modular tools head - Chłosta, Mirosław; Klusek, Konrad; Kobiałka, Janusz; Welc, Marcin (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
The orbital and radial riveting is one of the metal forming processes which enables the manufacture of products through cold working. The riveting machine with modular shape of structure was presented. The main parts of it were shown. On the end the riveting process validating criteria and subsystem used to force and displacement measurements were described. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)